Psikoedukasi Pendidikan Seks untuk Meningkatkan Sikap Orangtua dalam Pemberian Pendidikan Seks - Isnatul Chasanah (JIP (Jurnal Intervensi Psikologi), 2018)
8-10 years old are the end period of children where children start to think logically, critically, creatively, and scientifically. Along with so much cases on child sexual violence, sex education is important to understand self, environment, and people around. Sex education is an effort to educate and direct proper sexual behavior in children. In Indonesia, sex education for children is still considered as taboo, especially at the age of early and middle age of children. Parents assume that sex education is inappropriate for young children. Psychoeducation needed to improve attitudes of parents in providing sex education on children. Subject of research are parents in grade III of SD Negeri M Malang (N=19). This research is pre-experiments research with one group pretest posttest design. The results showed an increase in parents attitudes before and after intervention (t =-2,932; p = 0.009). Thus, it can be concluded that the psychoeducation effective to improve the attitude of the parents in giving sex education on children